Dual impact of anaemia and chronic kidney disease on postpercutaneous coronary intervention outcomes: insights from the Japanese nationwide registry - Yohei Numasawa; Shun Kohsaka; Ken Kozuma; Kyohei Yamaji; Hideki Ishii; Tetsuya Amano; Akio Kawamura; Ryoma Fukuoka; Yoshihide Fujimoto; Takashi Nakayama; Yuichiro Mori; Masaki Ieda; et al. (Open Heart)
Background Anaemia and chronic kidney disease (CKD) are both established risk factors for bleeding events after percutaneous coronary intervention (PCI). These conditions often coexist; however, previous assessments of these factors individually may have led to an underestimation of their impact on clinical outcomes.Methods We analysed the data of 77 482 patients who underwent PCI between 2017 and 2020 in the Japanese nationwide PCI registry. Based on preprocedural anaemia (haemoglobin: <13 g/dL in men; <12 g/dL in women) and CKD (estimated glomerular filtration rate, <60 mL/min/1.73 m²) statuses, the patients were categorised into ‘neither anaemia nor CKD’ (n=36 629; 47.3%), ‘CKD alone’ (n=17 120; 22.1%), ‘anaemia alone’ (n=10 136; 13.1%) and ‘both anaemia and CKD’ (n=13 597; 17.5%) groups. The study endpoints included bleeding (fatal or non-fatal major bleeding) and ischaemic (cardiovascular death, non-fatal acute coronary syndrome or non-fatal ischaemic stroke) events.Results The 1-year incidence of bleeding and ischaemic events was highest in the ‘both anaemia and CKD’ group and lowest in the ‘neither anaemia nor CKD’ group. After adjustment, ‘anaemia alone’ (HR 1.52; 95% CI 1.29 to 1.79; p<0.001) and ‘both anaemia and CKD’ (HR 1.39; 95% CI 1.18 to 1.63; p<0.001), but not ‘CKD alone’ (HR 1.00; 95% CI 0.85 to 1.17; p=0.97), were significantly associated with high risks of bleeding events compared with ‘neither anaemia nor CKD’. All three groups had higher ischaemic risk compared with ‘neither anaemia nor CKD’ (‘CKD alone’: HR 1.29; 95% CI 1.16 to 1.45; p<0.001, ‘anaemia alone’: HR 1.40; 95% CI 1.22 to 1.60; p<0.001, ‘both anaemia and CKD’: HR 1.61; 95% CI 1.43 to 1.81; p<0.001).Conclusions Anaemia increased bleeding risk regardless of CKD status, whereas ‘CKD alone’ did not. In addition, patients with anaemia and/or CKD were at a higher risk of ischaemic events. Clinicians should routinely perform initial risk assessments stratified by anaemia and CKD for patients undergoing PCI.